2017
DOI: 10.22159/ijcpr.2017v9i5.22128
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Phytochemical Screening and Anti-Inflammatory Effect of the Aqueous Extract of Tabernaemontana Divaricata Flower in Wister Rats

Abstract: Objective: To determine the phytochemical analysis and anti-inflammatory effect of the aqueous extract of Tabernaemontanadivaricata flower in Wister Rats.Methods: The aqueous extract of fresh flowers of the plant Tabernaemontanadivaricata (family-Apocyanaceae) were prepared and analyzed for phytochemical constituents using standard methods. The anti-inflammatory activity of the plant extracts was examined with the help of rat models by taking diclofenac as a standard drug against T. divericata oil extract by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For centuries, several Tabernaemontana species, such as T. divaricata , T. catharinensis , T. crassa , and T. elegans , have been exploited in traditional and folk medicine for the treatment of illnesses and the prevention of diseases and ailments, such as sore throat, hypertension, abdominal pain, and pulmonary disease [ 9 , 20 , 70 , 71 , 72 ]. A variety of chemical compounds extracted from many parts of Tabernaemontana species reportedly contain alkaloids, which exhibit biological activities, such as antimicrobial, antioxidant, anti-inflammatory, anticholinesterase, antineurodegenerative, anticancer, antidiabetic, antivenom, larvicidal, antihypertensive, wound healing, analgesic, and many other activities [ 2 , 3 , 6 , 9 , 71 , 72 ]. The details of the isolated compounds and respective pharmacological properties of a few Tabernaemontana species are summarized in the following paragraphs.…”
Section: Major Bioactive Components and Biological Activities Of mentioning
confidence: 99%
See 2 more Smart Citations
“…For centuries, several Tabernaemontana species, such as T. divaricata , T. catharinensis , T. crassa , and T. elegans , have been exploited in traditional and folk medicine for the treatment of illnesses and the prevention of diseases and ailments, such as sore throat, hypertension, abdominal pain, and pulmonary disease [ 9 , 20 , 70 , 71 , 72 ]. A variety of chemical compounds extracted from many parts of Tabernaemontana species reportedly contain alkaloids, which exhibit biological activities, such as antimicrobial, antioxidant, anti-inflammatory, anticholinesterase, antineurodegenerative, anticancer, antidiabetic, antivenom, larvicidal, antihypertensive, wound healing, analgesic, and many other activities [ 2 , 3 , 6 , 9 , 71 , 72 ]. The details of the isolated compounds and respective pharmacological properties of a few Tabernaemontana species are summarized in the following paragraphs.…”
Section: Major Bioactive Components and Biological Activities Of mentioning
confidence: 99%
“…Subsequently, these changes imitate the restoration of inflamed tissue and constrain additional damage to the organism [ 109 ]. Based on the characteristics of inflammation, this composite process is divided into two major types known as acute and chronic inflammation [ 72 , 109 , 113 ]. Acute inflammation occurs almost instantly, or a few hours following injury, and usually displays symptoms of redness, heat, and edema [ 72 ].…”
Section: Major Bioactive Components and Biological Activities Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the phytochemistry and presence of associated chemicals like alkaloids, terpenoids, steroids, flavonoids, phenyl propanoids, phenolic acids and enzymes in the leaves, stems, and roots [3][4] . A variety of chemical compounds extracted from many parts of Tabernaemontana species reportedly contain alkaloids, which exhibit biological activities, such as antimicrobial, antioxidant [5][6] , anti-inflammatory,anticholinesterase, antineurodegenerative, anticancer, antidiabetic, antivenom, larvicidal, antihypertensive, wound healing, analgesic, astringent, antioxidantanxiolytic, anti diabetic and anticonvulsant [7][8][9] and many other activities [10][11][12][13][14][15] . In this study, qualitative and quantitative phytochemical analysis was performed to identify the presence of various phytoconstituents in different leaf extract of T. divericata with standard procedures.…”
Section: Introductionmentioning
confidence: 99%